2020
DOI: 10.3390/pharmaceutics12070624
|View full text |Cite
|
Sign up to set email alerts
|

Postbiotic-Enabled Targeting of the Host-Microbiota-Pathogen Interface: Hints of Antibiotic Decline?

Abstract: Mismanagement of bacterial infection therapies has undermined the reliability and efficacy of antibiotic treatments, producing a profound crisis of the antibiotic drug market. It is by now clear that tackling deadly infections demands novel strategies not only based on the mere toxicity of anti-infective compounds. Host-directed therapies have been the first example as novel treatments with alternate success. Nevertheless, recent advances in the human microbiome research have provided evidence that com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 299 publications
(284 reference statements)
1
12
0
1
Order By: Relevance
“…This was shown for instance in the protection against pneumococcal colonization upon intranasal administration of Lactobacillus murinus [29]. While further studies are needed to determine which, if any, microbial species are associated with protection from Aspergillus infection, our study shows that, alternatively, it is possible to resort to microbial metabolites to improve antifungal resistance in the lung, as previously reported for indole-3-carboxaldehyde, produced by the gut microbiota [30] and able to protect from allergic bronchopulmonary aspergillosis [31] and Aspergillus pneumonia [17]. In this manuscript, we show that SCFAs are present in the lung during infection.…”
Section: Discussionsupporting
confidence: 77%
“…This was shown for instance in the protection against pneumococcal colonization upon intranasal administration of Lactobacillus murinus [29]. While further studies are needed to determine which, if any, microbial species are associated with protection from Aspergillus infection, our study shows that, alternatively, it is possible to resort to microbial metabolites to improve antifungal resistance in the lung, as previously reported for indole-3-carboxaldehyde, produced by the gut microbiota [30] and able to protect from allergic bronchopulmonary aspergillosis [31] and Aspergillus pneumonia [17]. In this manuscript, we show that SCFAs are present in the lung during infection.…”
Section: Discussionsupporting
confidence: 77%
“…This finding suggests that the control of the microbial composition and fitness could be an additional mechanism through which 3-IAld may exert its therapeutic activity at the host/microbe interface. In an in vitro study, we have shown that 3-IAld exhibited potent antimicrobial activity against the relevant respiratory pathogens in CF, such as Staphylococcus aureus and Pseudomonas aeruginosa [ 44 ]. These observations indicate that 3-IAld influences the composition of airways and gut microbiota, and may exert some degree of antimicrobial activity against CF pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…One intervention aimed to treat bacterial diarrhea is antibiotic therapy, although it is generally not recommended (with some exceptions). Moreover, many pathogenic strains have developed resistance to antibiotics [ 10 ]. On the other hand, there is the increasing concern that some probiotics harvest antibiotic-resistant genes in their genome that can be transferred to other potentially pathogenic bacteria [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%